Cholecystokinin-Like Peptide (DSK) in Drosophila, Not Only for Satiety Signaling - Nässel, Dick R.; Williams, Michael J. (Frontiers in Endocrinology, 2014)
Cholecystokinin (CCK) signaling appears well conserved over evolution. In Drosophila the CCK-like sulfakinins (DSKs) regulate aspects of gut function, satiety and food ingestion, hyperactivity and aggression, as well as escape-related locomotion and synaptic plasticity during NMJ development. Activity in the DSK-producing neurons is regulated by octopamine. We discuss mechanisms behind CCK function in satiety, aggression and locomotion in some detail and highlight similarities to mammalian CCK signaling.